Prevalence of non-Hodgkin lymphoma patients at high-risk of failure after CAR T-cell therapy eligible for bridging radiation therapy - Danish, Adnan; Della Pia, Alexandra; Fogel, Lindsay; Alkhatatneh, Hassan; Zhao, Charles; Varughese, Tony; Al Feghali, Karine A.; Pascual, Lauren; Sinclaire, Brittany; Marafelias, Michael; Zenreich, Joshua; Kuo, Yen-Hong; et al. (Frontiers in Oncology, 2024)
Background and purpose: To determine the prevalence of relapsed or refractory (R/R) non-Hodgkin lymphoma (NHL) patients meeting high-risk criteria for early relapse after CD19 CAR T-cell therapy (CART) who have disease encompassable in a standard radiation therapy (RT) plan (defined as <5 malignant lesions) and may benefit from bridging RT prior to CD19 CART. Materials and methods: This is a single-center, retrospective study of patients with R/R NHL who received CD19 CART from 2018 to 2022. Eligible patients had pre-apheresis radiologic studies available. All patients were classified by number of lesions and history of high-risk disease criteria: bulky disease ≥10 cm, ≥1 extranodal (EN) sites, LDH ≥normal, or ≥1 lesion with SUVmax ≥10. Results: Eighty-one R/R NHL patients were evaluated. Based on our definition, 40 (49%) patients would have been eligible for bridging RT, including 38 patients who met high-risk criteria: 31 with ≥1 EN site, 19 had ≥1 lesion with SUVmax ≥10, 16 with bulky disease, and 3 with elevated LDH. At 3 months after CART, ORRs in high-risk patients with <5 lesions, ≥5 lesions, and no lesions on pre-apheresis studies were 76% (CR 69%, PR 7%), 70% (CR 60%, PR 10%), and 80% (CR 80%), respectively. Conclusion: Approximately 47% (38/81) patients were classified as at high-risk of relapse after CART with disease encompassable in a standard radiation plan and eligible for bridging RT studies.